If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -3y) * 2 + 18xy = 0 Reorder the terms for easier multiplication: 2(3x + -3y) + 18xy = 0 (3x * 2 + -3y * 2) + 18xy = 0 (6x + -6y) + 18xy = 0 Reorder the terms: 6x + 18xy + -6y = 0 Solving 6x + 18xy + -6y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6y' to each side of the equation. 6x + 18xy + -6y + 6y = 0 + 6y Combine like terms: -6y + 6y = 0 6x + 18xy + 0 = 0 + 6y 6x + 18xy = 0 + 6y Remove the zero: 6x + 18xy = 6y Combine like terms: 6y + -6y = 0 6x + 18xy + -6y = 0 Factor out the Greatest Common Factor (GCF), '6'. 6(x + 3xy + -1y) = 0 Ignore the factor 6.Subproblem 1
Set the factor '(x + 3xy + -1y)' equal to zero and attempt to solve: Simplifying x + 3xy + -1y = 0 Solving x + 3xy + -1y = 0 Move all terms containing x to the left, all other terms to the right. Add 'y' to each side of the equation. x + 3xy + -1y + y = 0 + y Combine like terms: -1y + y = 0 x + 3xy + 0 = 0 + y x + 3xy = 0 + y Remove the zero: x + 3xy = y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 1.15=(1+x)(1+x)(1+x)(1+x)(1+x)(1+x)(1+x)(1+x)(1+x)(1+x)(1+x)(1+x) | | 4x/3+=2 | | -2x+6=-7x+14 | | 4(3x-2)-5(2-x)= | | 17.01y=6.3 | | 9a-6(a+5)= | | .2*n=48 | | (X/4)+3=5 | | 5p-2=9p-2 | | 14c-6=7c-6 | | 10f+4=3f-59 | | 12x-(x*x)=36 | | 3(2a-3b)-4b(4a-4)= | | Z^2+6z-20=00 | | -6w-45=-9(w+8) | | 9x-5y=12 | | Z^2+6x-16=0 | | 50x^2+15x-2=(5x+2) | | 4p-1=9+17 | | 6x-10=6+10 | | 9q+1=4q-44 | | 2=3c+11 | | 4x+40=12x-102 | | (3/2)+4=5 | | x(8+9)= | | 3x/4-3.2=5.3-2x/3 | | 17b=36+3b | | -3c-32=4c+3 | | 5cos^2x-3=0 | | 50x^2-15x-2=(5x+2) | | 5x+12=4x | | 114(4-6y)+5(13y+1)=-9 |